BENARKAH KEPEMIMPINAN HARUS BERADA DI TANGAN SUKU QURAISY? (Kajian Tematik Hadits Tentang Supremasi Kepemimpinan Suku Quraisy) - Made Saihu; Fatkhul Mubin (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2022)
This paper is about the leadership of the Quraysh in the hadith perspective. In this paper, it isexplained that the political embodiment is characterized by the legitimacy of the authority of the Quraysh as the only party entitled to hold power (caliph), especially the dominance of quraysh derived from the hadith of the Prophet SAW.  they are with power. It has been agreed by most mutakallimin that taklif has nothing to do except with the deeds of the servant he is able to do. And keeping the Nasab of Quraysh until the doomsday is something beyond human ability.